Wrocław 65+. The efforts targeted at seniors held by local government, NGOs, commercial enterprises, churches, and other public bodies dedicated to seniors - Sanecka, Anna (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
Ageing of the Polish society cause the growing number of proposals dedicated to seniors. This offers are extended by local governments as well as universities and study centres, churches and NGOs. Wrocław likes to be exceptional in many different areas. Wrocław authorities as well as city residents like if it is described as “young city” or multicultural one. It is understandable that they try to present the city as “seniors-friendly” as well. The article is not aimed to proclaim the city seniors-friendly or not, but to present some of the efforts offered to elder residents of Wrocław as well as to underline the distinctive attributes of such proposals together with some risks arising from these attributes.